Paradigma Thomas Khun Transformasi Pemasaran Tradisional Versus Pemasaran Digital - Nora Anisa Br Sinulingga; Binsar Sihombing; Yoel Putra Pratama Sitepu (Journal Economic Excellence Ibnu Sina, 2023)
Thomas Kuhn, a prominent philosopher of science, introduced the concept of scientific revolution through his famous theory. The linkage of science with marketing science opens the door to a deeper understanding of consumer behavior and market dynamics. The marketing phenomenon in Indonesia reflects a unique blend of tradition and modernity. This research uses the method of descriptive analysis method to analyze the data, where the data is reviewed and investigated in three stages; general, exploratory, and focused study. This research uses the descriptive analysis method to analyze the data (Sugiyono, 2014). Data were reviewed and investigated in three stages; general, exploratory, and study focus. In this study, the use of Thomas Kuhn's theory, as illustrated in "The Structure of Scientific Revolutions," provides a rich perspective on the paradigmatic evolution in marketing. Paradigms, as frameworks of shared understanding, play a central role in shaping scientific mindsets and marketing strategies.